The Rolling Motion Light Painting Blur as the Jouvenile’s New Innovation Phenomenon in 2020’s: Lukisan Cahaya Gerak Bergulir Kabur Sebagai Fenomena Inovasi Baru Jouvenile di Tahun 2020 - Soeharno, Ageng; Wicaksono, Itok (Universitas Muhammadiyah Jember, 2024)
Photography is a word from the Greek